Accounting for Production Sharing Contracts (PSCs) in the Context of Global Oil Price Uncertainty - Ayu Sapitri; Rina Tjandrakirana DP (Escalate : Economics and Business Journal, 2026)
Global oil price volatility disrupts upstream oil and gas stability, complicating Production Sharing Contracts (PSCs) through challenges in accounting treatment, revenue recognition, and asset valuation. This study aims to evaluate PSC accounting concepts and analyze oil price fluctuation impacts on financial reporting. Employing a qualitative Systematic Literature Review (SLR), the population comprises Scopus- and SINTA-indexed journals (2018-2026); the sample includes 20 relevant publications selected via keywords like "PSC accounting" and "oil price volatility." Data were analyzed using content analysis to synthesize fiscal mechanisms and risks. Results show Cost Recovery offers contractor safeguards but bureaucratic hurdles, while Gross Split enhances adaptability via Variable Split yet demands efficiency; volatility triggers asset impairments, reserve downgrades, and DD&A spikes, mitigated by hedging. In conclusion, PSC resilience hinges on flexible fiscal policies, robust accounting systems, and risk management to ensure financial transparency amid energy transitions